A Content Analysis of the Elementary School Textbooks in Terms of Paying Attention to Social Education Goals in Iran’s System of Education - Sirous Mahmoodi; Hamid Reza Imani-far (Islām va ̒ulūm-i ijtimā̒ī, 2020)
The main goal in this study is an analysis and investigation of textbooks in elementary schools in terms of the concern for the goals of social education. The research method is descriptive and a content analysis type. The statistical population is composed of all textbooks of elementary school published in school year 1398-1399 SH. Three topics of Muṭāliʻāt Ijtimāī “Social Studies”, Hidyihāyi Āsimānī “Celestial Gifts” and “Farsi” composed in 15 volumes were assigned to the sample in a goal-oriented way. The findings showed that in elementary period, the most attention has been paid to the goals of “nurturing respect for individuals and observing their rights” (0.962 information load and 0.092 significance factor), “nurturing the spirit of enjoining good and forbidding evil” (0.944 information load and 0.090 significance factor), “nurturing the spirit of order in individual and social relations” (0.942 information load and significance factor 0.090). Besides, less attention has been paid to the goals of “nurturing the spirit of resistance against malicious propaganda” (information load 0.58 and significance factor 0.055), and “nurturing the spirit of respect for law and observing it” (information load 0.744 and significance factor 0.071). Altogether, the findings show that no sufficient attention has been paid to the goals of social education in the elementary school textbooks.